SIMILARITIES AND DIFFERENCES OF THE CATEGORY OF VOICE IN ENGLISH AND UZBEK LANGUAGES. - Ixtiyor G’ulomov; Aziz Mukhammadiev (Journal of new century innovations, 2024)
Annotation: One area of intense scientific interest is the study of ratio forms, as it offers important insights about voice forms. The article's goal is to examine the opinions of Uzbek and English academics about this linguistic issue. Citing examples from Uzbek and English literature, an extensive analysis of pertinent ideas aims to compare and contrast the terminology and techniques utilized in each language.